A Historical Outline of Byzantine Philosophy and Its Basic Subjects - Viglas, Katelis (Peitho. Examina Antiqua, 2010)
The article seeks to present an overview of the history of Byzantine philosophy. It takes its point of departure in the most important factors that influenced and shaped the Patristic thought. Subsequently, the paper considers the relative autonomy of Byzantine philosophy and offers a brief profile of major philosophers that contributed to the stream in the period from 9th to 15th century. From the numerous subjects that were taken into account by the most prominent Byzantine philosophers, the article discusses such issues as: the view of God, the problem of ‘conceptual realism’, the relationship between such ‘disci plines’ as logic, metaphysics, ethics, aesthetics and philosophical anthro pology. Furthermore, such questions as the place of man in the world, the scope of their freedom and the problem of evil are also touched upon here. The paper concludes with some remarks on the develop ment of Byzantine philosophy after the fall of Byzantium.